Ocean‐driven and topography‐controlled nonlinear glacier retreat during the Holocene: southwestern Ross Sea, Antarctica - Jones, R. S.; Gudmundsson, Hilmar; Mackintosh, A. N.; McCormack, F. S.; Whitmore, R. J. (Geophysical Research Letters, 2021)
Recent ice sheet mass loss in Antarctica has been attributed to an influx of warm ocean waters, which drove grounding‐line retreat and ice thinning. Episodic retreat and rapid thinning also occurred in the southwestern Ross Sea during the Holocene, which today accommodates cold ocean waters. We applied finite‐element ice‐flow modeling to investigate the roles of ocean temperature and bed topography in the deglaciation of this region. First, our experiments demonstrate that bed topography controlled the spatial pattern of grounding‐line retreat. Topographic pinning points limited the rate of ice loss until retreat progressed beyond a bathymetric threshold. Second, ocean thermal forcing determined the timing of this ice loss. Enhanced ocean‐driven melt is required during the Early‐to‐Mid Holocene to replicate geological records of deglaciation, possibly indicating that warm ocean waters were once present in this region. On multi‐centennial timescales, ocean temperature drove, while bed topography controlled, nonlinear rates of ice mass loss.